Heterogeneity in male and female farmers’ preference for a profit‐enhancing and labor‐saving technology: The case of Direct‐Seeded Rice (DSR) in India - Joshi, Pramod K.; Khan, Mohammed Tajuddin; Kishore, Avinash (Wiley, 2019)
Labor‐saving and income‐increasing technologies may affect women farmers differently from men. However, very few studies explicitly account for women's preferences for new technologies. We carried out a discrete choice experiment with 337 female and 329 male farmers in Maharashtra, India, to measure their willingness to pay (WTP) for direct‐seeded rice (DSR) with drum seeder and to understand the gender differences in marginal valuations of key attributes. We used the Women's Empowerment in Agriculture Index (WEAI) to collect self‐reported data on the role and say of women in different domains of decision making. The respective gender roles of women and men in the family and on the farm are aligned with their preferences. Men have a greater say over how the family spends the cash. Accordingly, men tend to have a higher WTP for attributes that increase income (increase in yield) or reduce cash costs (reduction in seed rate). Women contribute a large share of the labor for transplanting rice, much of which is unpaid work on family farms. Women, therefore, seem to value labor saving more. Women in our sample were more interested in the new technology and had a higher WTP for it.